(untitled) (Medical Forum Monthly, 2024)
Objective: To compare the outcomes of standard and totally tubeless percutaneous nephrolithotomy in treating renal stones in terms of postoperative analgesia requirement, operative time and mean duration of hospital stay. Study Design: Randomized controlled trial Place and Duration of Study: This study was conducted at the Department of Urology, Nishtar Hospital, Multan, from December 2022 to November 2023. Methods: A sample size of 88 (44 in each group) were enrolled in the study. Group A was receiving standard percutaneous nephrolithotomy (PCNL), while Group B was receiving the totally tubeless PCNL Analgesics were administered when the patient reports a VAS pain score above a predefined threshold (e.g., ≥4 out of 10). The requirement for postoperative analgesia within a 48-hour period will be recorded. Results: The mean analgesic requirement of standard PCNL group was greater than totally tubeless PCNL group as 20.79±3.08 mg and 9.71±1.65 mg, respectively. The mean hospitalization time of standard PCNL group was greater than totally tubeless PCNL group3.31±1.08 days and 1.82±0.54 days. Conclusion: Totally tubeless PCNL is effective and safe technique, making it a viable option for patients with renal stones. This approach is linked to reduced pain, decreased analgesic requirements, shorter operation times, and decreased hospitalization durations.